RECOMBINATION RATE COEFFICIENTS OF BORON-LIKE Ne - (:unkn) unknown (IOP PUBLISHING LTD, 2013)
Recombination of Ne5+ was measured in a merged-beam type experiment at the heavy-ion storage ring CRYRING. In the collision energy range 0-110 eV resonances due to 2s(2)2p -> 2s2p(2) (Delta n=0) and 2s(2)2p -> 2s(2)3l (Delta n=1), core excitations were observed. The experimentally derived rate coefficients agree well with the calculations obtained using AUTOSTRUCTURE. At low energies, recombination is dominated by resonances belonging to the spin-forbidden 2s2p(2)(P-4(J))nl series. The energy-dependent rate coefficients were convoluted with a Maxwell-Boltzmann electron energy distribution to obtain plasma recombination rate coefficients. The data from the literature deviate from the measured results at low temperature.
Keywords: atomic data; atomic processes; plasmas; ELECTRON-ION RECOMBINATION; OPTICALLY THIN PLASMAS; DIELECTRONIC RECOMBINATION; RADIATIVE RECOMBINATION; IONIZATION EQUILIBRIUM; C-II; SOLAR; ABUNDANCES; ENERGY; CARBON